"Genealogy of Filipino traits" an illustrated anthology of Filipino psychology and history - Uy, Laija Nikki Marie M.
A form of stereotyping can be observed in today's Filipinos. Stereotypes or generalizations are assumptions made by a certain person or group regarding their perception of the other's identity and culture. In cultural stereotypes, one's attention focuses on the features that were imparted to him as the typical expected feature in that person, therefore confirming and strengthening his stereotype. Stereotypes are not only applicable on how a collective perceives another culture. It is also applicable within a group. A lot of Filipinos perceive their own race's values as "negative", labeling various as having worked against the ideas and goals of a Filipino nation (Jocano, 1992), many are doubtful and convinced that much of their values are negative or flawed, identifying them as a hindrance to development or damaging to culture. The negativism in values and traits has caused generations of self-doubt, cynicism, and self-destruction - a fixation only on the negative aspects of a bipolar value, rendering a nation doubtful and critical to one's own culture. The researcher found out during her research that due to misconception and misinformation, negative stereotyping in cultural traits will continue to occur. Knowledge regarding the historical origin of said traits is needed in order to be able to affect understanding of the Filipino about own cultural traits and values based from the data that she was able to collate. One should also not only highlight the positive side but also give explanation about the negative aspect of these stereotyped traits to be able to give a cleared perspective regarding the topic. The creative output utilized was an anthology of writings by outstanding persons in the field of sikolohiyang Filipino and history for all the traits collected, illustrations were made for publication that catered to the target audience. Campaign collateral were also made in able to promote the book